'I left because…': Caribbean high-skilled emigrants' reasons to migrate to the US. Issue 2 (17th February 2023) - Brissett, Nigel O. M.
ABSTRACT: The rate of emigration of highly educated people from the Caribbean is one of the highest in the world but little research exists on this phenomenon. This paper helps to fill this gap by focusing on one particular subset of Caribbean skilled emigrants, those working in higher education in the US, including academics and administrators. Drawing on an inductive methodology, and using data from interviews, this interdisciplinary research assesses why these high-skilled Caribbean people emigrate from the region, and the factors that facilitate their immigration to the US. Findings indicate that, ultimately, high skilled emigration of this group is complex, reflecting a compelling interdisciplinary understanding of skilled emigration that has resonance in network, neoclassical human capital, and world systems theories of skilled emigration from the Caribbean.